2016
DOI: 10.1111/psyp.12806
|View full text |Cite
|
Sign up to set email alerts
|

Optimism moderates psychophysiological responses to stress in older people with Type 2 diabetes

Abstract: Optimism is thought to be beneficial for health, and these effects may be mediated through modifications in psychophysiological stress reactivity. Type 2 diabetes (T2D) is associated with reduced cardiovascular responses to stress and heightened cortisol over the day. This study assessed the relationships between optimism, stress responsivity, and daily cortisol output in people with T2D. A total of 140 participants with T2D were exposed to laboratory stress. Heart rate (HR), systolic (SBP), diastolic blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 71 publications
6
21
1
3
Order By: Relevance
“…These six indicators were also used in the 100-thousand-scale cohort studies in Japan, such as the Japan Public Health center-based prospective study and the Japan Gerontological Evaluation study 24,25 . LOT-R, laughter, ESSI and SNI were also shown to be applicable to diabetes patients [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 93%
“…These six indicators were also used in the 100-thousand-scale cohort studies in Japan, such as the Japan Public Health center-based prospective study and the Japan Gerontological Evaluation study 24,25 . LOT-R, laughter, ESSI and SNI were also shown to be applicable to diabetes patients [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 93%
“…In addition, a high level of optimism could help avoid exaggerated stress reactions and modulate “stress‐related autonomic and neuroendocrine dysregulation” (Puig‐Perez et al, , P536), which could buffer the influence of stress on health behaviour. The finding suggests that improving patients’ optimism self‐management programme (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Optimism is an important inner strength which plays a protective role to avoid exacerbation of illness (Nabi et al, ). It is suggested that having an optimistic state of mind can improve confidence and motivation and modulate stress‐related neuroendocrine dysregulation, promoting the achievement of goals (Puig‐Perez, Hackett, Salvador, & Steptoe, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, a highly estrogenic environment like that of IVF may cause HPA activation and premature release of luteinizing hormone (LH) [64] . Second, release of corticotrophin-releasing hormone would increase cortisol and inhibit estradiol production [65][66][67] . A longitudinal study [9] on emotional adjustment vis-à-vis fertility treatment cycles had women and their spouses complete pre-, post-, and delayed post-questionnaires to assess state anxiety, depression, neuroticism, optimism, infertility-related cognitions of helplessness and acceptance, coping, and self-evaluated social support.…”
Section: Optimism and Resilience In Infertilitymentioning
confidence: 99%